Biosurfactant-Enhanced Remediation of Oil-Contaminated Environments - A. Shulga; E. Karpenko; R. Vildanova-Martsishin; A. Turovsky; M. Soltys (Adsorption Science & Technology)
The development of new efficient cleaning technologies for the bioremediation of the environment and its cleaning from oil products has become a subject of great interest. Surfactants influence the bioremediation of oil and other organic contaminants through increasing their availability. Since surfactant products of a microbial nature are highly efficient in this respect, they have important advantages over synthetic materials. Being biodegradable, they are ecologically safe. A new washing bioremedy based on surfactant products synthesized microbially from the bacterial strain Pseudomonas sp. PS-17 has been obtained. It contains an unique biocomplex of a glycolipid biosurfactant and an alginate biopolymer and possesses a high surface and emulsifying activity. The washing and antisorptional capacity of this bioremedy has been tested on objects of various natures, viz. bird feathers, animal skins and furs. We have obtained positive results in the remediation of sea sands, birds and animals suffering from ecological catastrophy. It was shown that the bioremedy has mild properties and does not change the structure of the feathers, skins and furs studied. The bioremedy remains active over the temperature range 15–90°C.